The role of physical education and sports in the consolidation of some values of citizenship among students in secondary education. Descriptive study of some secondary schools - Batna - - Kadri, Abdelhafid; Mallam, Abdelmalek (Journal of Human Sciences, 2021)
The consolidation of the values of citizenship in any society is urgent, Especially in light of globalization and its burdens, hence the goal of this research to show the extent of students’ awareness of the concept of citizenship, And clarify the role of the professor and the share of physical education and sports in the consolidation of some values of citizenship in a sample of secondary school students, For this purpose, the researchers used the descriptive approach. The research sample consisted of (31) teachers in the state of Batna, It also consisted of (102) students and students from the secondary level, who were chosen intentionally, where the researchers distributed two questionnaires ,the first directed to the teachers and the second to the students, And to analyze the data we relied on the Statistical Package for Social Sciences (PASW V26), to arrive at a moderate awareness of the concept of citizenship, and to the prominent and large role in the contribution of the professor and the class of physical education and sports in establishing some of its values.